Pemberdayaan Perempuan Adat melalui Kapabilitas Keuangan: Perilaku Pengelolaan Keuangan dalam Ekonomi Informal di Indonesia Timur - Aprianto La’lang Kuddy; Hesti Murwaniputri; Pisi Bethania Titalessy (Society, 2025)
Income inequality and economic marginalization continue to affect indigenous women in Eastern Indonesia, particularly those engaged in informal economic activities such as traditional market trading. These women often act as primary breadwinners, managing household finances under persistent income constraints. This study investigates how financial capability, the combined influence of financial knowledge and attitude, affects financial management behavior among indigenous women micro-entrepreneurs. Using a quantitative explanatory design, data were collected through structured questionnaires from 82 active traders in Jayapura Regency and analyzed using multiple regression techniques. The findings show that both financial knowledge and attitude have a statistically significant and positive impact on financial management, individually and collectively. These results suggest that strengthening financial capability is crucial for enhancing indigenous women's economic resilience and decision-making autonomy in the informal economy. This study contributes to the literature on gendered financial behavior and provides practical insights for local governments and development agencies aiming to design targeted financial literacy interventions in marginalized communities.